PENGARUH PEMANFAATAN APLIKASI E-SPT MASA PPN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK (Studi pada Kantor Pelayanan Pajak (KPP) Pratama Surabaya Genteng) - Kharisma, Nani (Jurnal Mahasiswa Perpajakan, 2014)
The purpose of this research is to know and analyze simultaneously the influence and effect of partially between the perspective of Taxpayer (X1), The readiness of technology(X2), public services (X3), and socialization model (X4) toward tax compliance and to know the dominant variable between the free against taxpayer compliance rate to variables is not as free. This research was conducted by explanatory research with quantitative approach. The amount of Taxpayer population is 3.565 that based on Taxpayer who have reported monthly Tax Return by using e-VAT return period since January until June 2013 at Tax Office Surabaya Genteng which was taken by Accidental Sampling technique with amount questionnaire 97 taxpayers who reported the e-VAT return period. The Data Analysis that was used in this research is descriptive analysis, and multiple linear regressions to the hypothesis test using f test and t tes. The result of this research are those kind of variable that consist of the perspective of Taxpayer (X1), The readiness of technology(X2), public services (X3),and socialization model (X4) are influenced significantly toward Taxpayer compliance (Y) both simultaneously and partially. The variable of Taxpayer perspective is dominant variable that affect to the Taxpayer Compliance. Keyword : Montly E-SPT of VAT, the perspective of Taxpayer ,The readiness of technology, public services and socialization model, Taxpayer Compliance